-5(6-x)+6=4-7(x-2)

Simple and best practice solution for -5(6-x)+6=4-7(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(6-x)+6=4-7(x-2) equation:


Simplifying
-5(6 + -1x) + 6 = 4 + -7(x + -2)
(6 * -5 + -1x * -5) + 6 = 4 + -7(x + -2)
(-30 + 5x) + 6 = 4 + -7(x + -2)

Reorder the terms:
-30 + 6 + 5x = 4 + -7(x + -2)

Combine like terms: -30 + 6 = -24
-24 + 5x = 4 + -7(x + -2)

Reorder the terms:
-24 + 5x = 4 + -7(-2 + x)
-24 + 5x = 4 + (-2 * -7 + x * -7)
-24 + 5x = 4 + (14 + -7x)

Combine like terms: 4 + 14 = 18
-24 + 5x = 18 + -7x

Solving
-24 + 5x = 18 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-24 + 5x + 7x = 18 + -7x + 7x

Combine like terms: 5x + 7x = 12x
-24 + 12x = 18 + -7x + 7x

Combine like terms: -7x + 7x = 0
-24 + 12x = 18 + 0
-24 + 12x = 18

Add '24' to each side of the equation.
-24 + 24 + 12x = 18 + 24

Combine like terms: -24 + 24 = 0
0 + 12x = 18 + 24
12x = 18 + 24

Combine like terms: 18 + 24 = 42
12x = 42

Divide each side by '12'.
x = 3.5

Simplifying
x = 3.5

See similar equations:

| ay^2+7y-8ay=56 | | 7/4=5/b | | xy*dx-(2x+4y)*dy=0 | | 2*2+y=-5 | | 2*1+y=-5 | | -3x=17+3y-z | | 2*0+y=-5 | | (4x-9)(64x^2-9)=0 | | y^2*dy=x(xdy-ydx)e^x/y | | m^3+2m^2-63m=0 | | 2(2x^2+y^2)*dx-xy*dy=0 | | [x^2+7x-71]=27 | | (2y-5)(3y+7)=0 | | 144=x+38 | | 3x-5(x-3)=-7+2x-10 | | 4*2+y=8 | | p-3u=3k | | 4*1+y=8 | | -3k=3u+-p | | 2(b-24)=44-4(b-4) | | x(x-3)(x+8)=0 | | 4*2-y=0 | | 7(w-5)=28 | | 3x-5=3-7 | | 8(x-5)(x+5)=0 | | 4*1-y=0 | | (3a+8b)(-6)= | | 4*0-y=0 | | -4+6=10 | | 5m+3=19 | | 3(3x^2+y^2)*dx-2xy*dy=0 | | 20log(x)=18.85 |

Equations solver categories